PENGARUH PENGGUNAAN CUTTING FLUID DAN PEMILIHAN FEED RATE TERHADAP KEKASARAN PERMUKAAN DAN KEPRESISIAN MATERIAL ALUMINIUM MENGGUNAKAN MESIN MILLING CNC - Widhaya Bastian Purnama (Jurnal Teknika, 2017)
There are many factor affecting the quality of product that are produced from milling machine process. The quality is mostly about surface roughness and precision. Those affecting factors are the selection of cutting parameter and use of cutting fluid. The research is done in order to know the effect of using cutting fluid and feed rate to aluminum on surface roughness and precision using Milling CNC machine. This research uses milling CNC Mitsubishi M70 machine. The free variables of feed rate are 20, 32, 45, 69, 108 mm/min. Each feed rate variations are given cutting fluid and no- cutting fluid treatment. The cutting fluid used is bromus oil which is mixed with water. The tests performed were surface roughness test, precision test. The result of this study shows that feed rate is in line with surface roughness. The use of cutting fluid affects surface roughness. The surface roughness score at feed rate variation using coolant treatment are 20, 32, 45, 69, 108 mm/min shows the surface roughness score of 0,442; 0,484; 0,553; 0,643; 0,797 μm. surface roughness score without cutting fluid treatment reveals the score of 0,470; 0,517; 0,582; 0;662; 0,847 μm. According to statistical analysis result using two way ANOVA, it can be concluded that the use of cutting fluid and feed rate affect precision at 95% trust rate. The measurement of A dimension using cutting fluid in the variation of feed rate 20, 32, 45, 69, 108 mm/min shows the precision rate of 99,999348; 99,99929; 99,999304; 99,999261; 99,9992 %. While, the variation without cutting fluid treatment reveals the precision rate at 99,999188 ; 99,999184; 99,999037; 99;998884; 99,998684 %